2009
DOI: 10.1121/1.3203805
|View full text |Cite
|
Sign up to set email alerts
|

Detection probability of vocalizing dugongs during playback of conspecific calls

Abstract: Dugongs (Dugong dugon) were monitored using simultaneous passive acoustic methods and visual observations in Thai waters during January 2008. Chirp and trill calls were detected by a towed stereo hydrophone array system. Two teams of experienced observers conducted standard visual observations on the same boat. Comparisons of detection probabilities of acoustic and visual monitoring between two independent observers were calculated. Acoustic and visual detection probabilities were 15.1% and 15.7%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…4) suggests that dugongs exchange vocalizations. The number of vocalizing dugongs also increased when a sequence of chirps and a trill was broadcast repeatedly during towed acoustic surveys (Ichikawa et al, 2009). The chirp ratio, or the repetition rate of chirps, was significantly higher after playback of any stimuli than that after a silence.…”
Section: A Calls Recorded After Stimulus Playbackmentioning
confidence: 96%
See 3 more Smart Citations
“…4) suggests that dugongs exchange vocalizations. The number of vocalizing dugongs also increased when a sequence of chirps and a trill was broadcast repeatedly during towed acoustic surveys (Ichikawa et al, 2009). The chirp ratio, or the repetition rate of chirps, was significantly higher after playback of any stimuli than that after a silence.…”
Section: A Calls Recorded After Stimulus Playbackmentioning
confidence: 96%
“…However, at least two wild dugongs vocalized almost concurrently on four occasions during the experiment. Furthermore, Ichikawa et al (2009) demonstrated that dugongs in the focal area vocally respond to playbacks of a chirp and trill sequence. These observations support the hypothesis that dugongs in the focal area exchange vocalizations.…”
Section: A Calls Recorded After Stimulus Playbackmentioning
confidence: 98%
See 2 more Smart Citations
“…Ichikawa et al (2009) demonstrated for wild dugongs in Thailand that playbacks of sounds of actual or synthetic dugong calls attracted dugongs to within 10 and 19 m, respectively, from within a 250 m radius. Playback of 3.5 kHz tones of 141 dB re 1 µPa at 1 m SL resulted in a stand-off distance of 100 m.…”
Section: Introductionmentioning
confidence: 99%